1999
DOI: 10.1161/01.atv.19.3.525
|View full text |Cite
|
Sign up to set email alerts
|

ApoA1 Reduces Free Cholesterol Accumulation in Atherosclerotic Lesions of ApoE–Deficient Mice Transplanted With ApoE–Expressing Macrophages

Abstract: Abstract-Along with apolipoprotein (apo) E, which promotes cholesterol efflux from foam cells, apoA1-containing high density lipoprotein (HDL) is thought to facilitate the transport of cholesterol from lesions. This role for apoA1 was tested in vivo by lethally irradiating apoE-deficient and apoE-plus apoA1-deficient mice and reconstituting them with bone marrow cells isolated from wild-type (WT) mice. ApoE, but not apoA1, was synthesized by the transplanted bone marrow-derived cells. Therefore, this transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 46 publications
2
49
0
Order By: Relevance
“…In another study, mice deficient in both apoE and apoA-I but expressing macrophage-derived apoE were found to have 2-to 3-fold lower plasma cholesterol than mice deficient in only apoE and expressing macrophage apoE. In spite of the lower plasma cholesterol, the apoA-I and apoE double knockout mice had atherosclerotic lesions 60% larger than in the apoE only knockout mice expressing macrophage apoE (9). More recently, using a method of monitoring the in vivo fate of radiolabeled macrophage cholesterol, a study showed that overexpression of liver-derived apoA-I promotes reverse cholesterol transport from macrophages to feces more efficiently than in mice with normal levels of plasma apoA-I (10).…”
mentioning
confidence: 97%
“…In another study, mice deficient in both apoE and apoA-I but expressing macrophage-derived apoE were found to have 2-to 3-fold lower plasma cholesterol than mice deficient in only apoE and expressing macrophage apoE. In spite of the lower plasma cholesterol, the apoA-I and apoE double knockout mice had atherosclerotic lesions 60% larger than in the apoE only knockout mice expressing macrophage apoE (9). More recently, using a method of monitoring the in vivo fate of radiolabeled macrophage cholesterol, a study showed that overexpression of liver-derived apoA-I promotes reverse cholesterol transport from macrophages to feces more efficiently than in mice with normal levels of plasma apoA-I (10).…”
mentioning
confidence: 97%
“…ApoE is also an acceptor for FC and phospholipid released from macrophages by ABCA1 (7). Additionally, apoE has been reported to stimulate cholesterol release from macrophages to apoA-I-containing acceptors (8)(9)(10). ApoE also enhances HDL or apoA-I interaction with vascular wall cells and extracellular matrix (11), activities that could contribute to the atheroprotection due to low-level apoE expression.…”
mentioning
confidence: 99%
“…94059, Harlan Teklad). 4 The mice were housed 4 per cage in autoclaved filter-topped cages with autoclaved water and kept on a 12-hour light-dark cycle. All procedures were performed in accordance with institutional guidelines.…”
mentioning
confidence: 99%